(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Raden I, Nugroho CC. Syahrani. 2017. Identification and characterization of morphological diversity of Lemba (Curculigo latifolia) in East Kalimantan, Indonesia. Biodiversitas 18: 1367-1376. Lemba (Curculigo latifolia) is Kalimantan’s land prospective for commercial cultivation because its leaf fiber has been traditionally utilized as fiber source for ulap doyo woven cloth; its fruit as sweetener; and its root as medicinal herb. To this days, only a few of research has been conducted on lemba in East Kalimantan or even in Indonesia, including studies on lemba plant phenotype suitable for weaving material. Thus, a research about identification and morphological characterization of lemba cultivars is necessary to identify and characterize lemba plant in East Kalimantan to reveal phenotypic variability in both quantitative and qualitative traits that can be utilized as the source of germplasm for the plant breeding program. This study was carried out in three Sub-districts, i.e.: Tenggarong Sub-district (Kutai Kartanegara District), Kota Bangun Subdistrict (Kutai Kartanegara District), and Jempang Sub-district (West Kutai District). Data collection was done by observation, and measurement of quantitative and qualitative traits of lemba plant. Descriptive analysis was applied on the morphological traits data, while correlation analysis was performed to reveal relationship between the qualitative and quantitative morphological traits by using software Minitab v.14.12. Phenotypic variability was determined based on the standard deviation. Principal component analysis and cluster analysis of the data were performed by using software SPSS v.11.6. The variance value of the 33 observed lemba plant accessions from the three Sub-districts indicated that the phenotypic variability of the qualitative traits was narrow while that of the quantitative traits was broad. There are three principal components that account for the observed variability with a cumulative variance of 96% which is obtained from 19 observed traits. Cluster analysis at similarity 95% indicates that there are five lemba accessions groups based on only qualitative, only quantitative, or based on combined qualitative and quantitative traits.